2020
DOI: 10.1123/ijspp.2019-0308
|View full text |Cite
|
Sign up to set email alerts
|

Improved Physical Performance and Decreased Muscular and Oxidative Damage With Postlunch Napping After Partial Sleep Deprivation in Athletes

Abstract: Purpose: To investigate the effects of napping after partial sleep deprivation (PSD) on reaction time, mood, and biochemical response to repeated-sprint exercise in athletes. Methods: Nine male judokas performed 4 test sessions in a counterbalanced and randomized order. Participants accomplished 1 control session after a normal sleep night (NSN) and 3 after PSD with (1) no nap, (2) ∼20-min nap (N20), and (3) ∼90-min nap (N90) opportunities. Test sessions included the running-based anaerobic sprint test, reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(119 citation statements)
references
References 38 publications
13
106
0
Order By: Relevance
“…For example, following a normal night sleep, it has been shown that (i) a 25-min nap opportunity enhanced performance during the 5mSRT [12], (ii) a 25-min, 35-min and 45-min nap opportunity increased physical performance during the 5mSRT [13], (iii) a 35-min and 45-min nap opportunity enhanced 5 jump performance [11], and (iv) a 45-min [11] and 90-min [10] nap improved attention estimated by the digit cancelation test (DCT). After partial sleep deprivation, 30-min of napping improved sprint performance and alertness [14,16], and 20-min and 90-min of napping enhanced repeated sprint performance [15,17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, following a normal night sleep, it has been shown that (i) a 25-min nap opportunity enhanced performance during the 5mSRT [12], (ii) a 25-min, 35-min and 45-min nap opportunity increased physical performance during the 5mSRT [13], (iii) a 35-min and 45-min nap opportunity enhanced 5 jump performance [11], and (iv) a 45-min [11] and 90-min [10] nap improved attention estimated by the digit cancelation test (DCT). After partial sleep deprivation, 30-min of napping improved sprint performance and alertness [14,16], and 20-min and 90-min of napping enhanced repeated sprint performance [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…More than 1 h was allowed for participants to overcome any sleep inertia that might have occurred after napping. In fact, 30 min has been shown as sufficient to overcome sleep inertia [15][16][17].…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations